A treatise on Christian Banking - Bøsterud, Morten (AOSIS, 2021)
From a moral perspective, all banking practice and theory can be seen as value driven. Therefore, there will be no such thing as value-neutral banking activities, and the application of Christian ethical and pastoral principles adds insights to the field of banking for all its involved stakeholders. This book contributes to the specific scientific discourse of practical theology, as this typically appears within the subfields of ethics and pastoral studies. Christian ethics and pastoral principles as applied in banking make up a largely neglected area in the wider academic discourse found within practical theology, and the research presented in this book contributes new knowledge to the field, with particular emphasis on banking practice. It is expected that the theories presented herein will be of interest for other scholars, not only within the realm of practical theology, but also in a cross-domain perspective where scholars in a broad field of disciplines may find the research and academic positions of interest. Such academic fields would include economics, finance, business administration, sociology, history, anthropology, and perhaps more. This expectation may not least be derived from the increasing focus on Corporate Social Responsibility (CSR), as this has emerged over the last decades within the wider business realm in general, whence the world of banking has followed suit. Alongside this development, an emergence of Islamic banking has been seen, which has showed substantial growth and success.